Neonatal developmental and behavioral outcomes of immediate delivery versus expectant monitoring in mild hypertensive disorders of pregnancy: 5-year outcomes of the HYPITAT II trial. (January 2020) - Zwertbroek, Eva F.; Zwertbroek, Julia; Broekhuijsen, Kim; Franssen, Maureen T.M.; Ganzevoort, Wessel; Langenveld, Josje; Mol, Ben W.J.; van Pampus, Marielle; Scherjon, Sicco; van Baar, Anneloes L.; Groen, Henk; ,
Abstract: Objective: To compare effects of immediate delivery vs expectant monitoring on neurodevelopmental and behavioral outcomes at 5 years of age in offspring of women with mild late preterm hypertensive disorders. Study design: We studied children born during the HYPITAT-II trial, in which 704 women with a hypertensive disorder between 34 and 37 weeks of gestation were randomized to immediate delivery or expectant monitoring. Participating women were asked to complete the Ages and Stages Questionnaire (ASQ) for developmental outcome and the Child Behavior Checklist (CBCL) for behavioral problems when their child was 5 years old. Outcomes were dichotomized and analyzed by logistic regression analysis. We also assessed factors influencing development and behavior at both 2 and 5 years after a hypertensive pregnancy. Results: Five years after the original study 322(46%) women were contacted for follow-up, of whom 148 (46%) responded. In the delivery group 22%(n = 14/65) of the children had an abnormal ASQ score compared to 21% (n = 13/62) in the expectant monitoring group (p = 0.9). Abnormal CBCL-scores were found in 19% (n = 14/72) of the children in the delivery group versus in 27% (n = 20/75) in the expectant monitoring group (p = 0.3). The main predictor of development and behavior at 2 and 5 years was fetal growth restriction (for abnormal development OR 2.1, CI 1.0–4.4; for behavior problems OR 2.2, CI 1.1–5.5). Higher maternal education decreased abnormal behavior outcomes (OR 0.5, CI 0.2–0.9) and a similar tendency was observed for developmental problems (OR 0.6, CI 0.3 – 1.1). Conclusion: We did not find different developmental and behavior outcomes at 5 years of age between a management policy of immediate delivery and expectant management in preterm hypertensive disorders. The increased risk of developmental delay at 2 years of age after immediate delivery, we found in the 2 year follow up study, did not persist at 5 years of age.